PUBLIC-PRIVATE PARTNERSHIP AND ITS ROLE IN THE ECONOMY OF A COUNTRY - Urokova , Laylo Akmaljon qizi (Educational Research in Universal Sciences, 2023)
A public-private partnership is an arrangement in a public sector project involving the private sector. It has been applied in many countries, especially to build infrastructure projects such as transportation systems, sewers, water systems, hospitals, energy, and information technology. This article discusses that public-private partnerships (PPPs) are an effective mechanism which will be successfully used in further development of the business environment, small business, and private entrepreneurship.